2020
DOI: 10.1007/s11596-020-2282-1
|View full text |Cite
|
Sign up to set email alerts
|

Tau in Alzheimer’s Disease: Pathological Alterations and an Attractive Therapeutic Target

Abstract: SummaryAlzheimer’s disease (AD) is an age-related neurodegenerative disease with two major hallmarks: extracellular amyloid plaques made of amyloid-β (Aβ) and intracellular neurofibrillary tangles (NFTs) of abnormally hyperphosphorylated tau. The number of NFTs correlates positively with the severity of dementia in AD patients. However, there is still no efficient therapy available for AD treatment and prevention so far. A deeper understanding of AD pathogenesis has identified novel strategies for the generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 162 publications
(198 reference statements)
0
5
0
2
Order By: Relevance
“…744 Tau is the major microtubule-associated protein of a mature neuron, and it is a central molecule in the pathogenesis of AD. 745 Previous studies have highlighted the importance of PTMs (e.g., O-GlcNAcylation, phosphorylation, and acetylation) of Tau in AD. [746][747][748] For example, the level of O-GlcNAcylation of tau in AD brain is reduced, and SIRT1 reduces O-GlcNAcylation of tau through CREB.…”
Section: ) Other Intestinal Diseasesmentioning
confidence: 99%
“…744 Tau is the major microtubule-associated protein of a mature neuron, and it is a central molecule in the pathogenesis of AD. 745 Previous studies have highlighted the importance of PTMs (e.g., O-GlcNAcylation, phosphorylation, and acetylation) of Tau in AD. [746][747][748] For example, the level of O-GlcNAcylation of tau in AD brain is reduced, and SIRT1 reduces O-GlcNAcylation of tau through CREB.…”
Section: ) Other Intestinal Diseasesmentioning
confidence: 99%
“…This mechanism was described for axonal microtubules in cultured neurons and seems to be essential for axonal transport [ 68 , 71 , 75 ]. Moreover, this region also interacts with other proteins, such as actin or heat shock proteins [ 76 , 77 ]. Due to its interaction with microtubules, Tau is a modulator in a number of cellular processes involving cytoskeletal structure, such as morphogenesis, cellular division, and intracellular trafficking of organelles and vesicles [ 68 , 69 ].…”
Section: Tau Isoformsmentioning
confidence: 99%
“…In our study, we found memory impairment was induced in STZ‐induced model according to the Morris water maze test, and PTS protected mice against memory deficit, which was consistent with a previous research (Meng et al, 2019). Aβ accumulation and hyperphosphorylated Tau are two cardinal pathological hallmarks of AD, which might be related to neuronal dysfunction and cognitive decline (Gu & Liu, 2020; Yu & Wu, 2021). Here we found that PTS weakened Aβ 1–42 accumulation and Tau hyperphosphorylation in AD mice, indicating that PTS might regulate Aβ and Tau pathology to inhibit AD progression.…”
Section: Discussionmentioning
confidence: 99%